MARKETING STRATEGY TO INCREASE SALES OF YUASA BATTERY BRAND AT CV HARKAT FAWWAZ SEJAHTERA - Rizky, Afrisandi Fatur; Sabir, Muh (Journal of Business And Entrepreneurship, 2023)
This study aims to determine the marketing strategies that need to be implemented and prioritized to increase sales of Yuasa brand batteries at CV Harkat Fawwaz Sejahtera. This research uses a descriptive method. In this study the data collection techniques used were observation, questionnaires, and documentation. To find out the future marketing strategy, the data analysis instrument used is Importance Performance Analysis (IPA). The results of this study indicate that the strategy that needs to be implemented is that the company needs to implement a warranty and return system and also provide discounts to consumers. In addition, the company must also increase sales promotion from various promotional media and the need for a delivery system and time discipline.